IMMUNE PATHOGENESIS OF PSORIASIS AND PSORIATIC ARTHRITIS - S. V. Smirnova; M. V. Smolnikova (Медицинская иммунология, 2014)
Significance of psoriasis (PS) research is determined by increasing incidence of this disorder, higher frequency of severe clinical forms, e.g., psoriatic arthritis (PsA). Clinical course and outcomes of psoriasis and psoriatic arthritis depend on degree of immunological disturbances and imbalance of cytokine regulation of intercellular interactions. The leading immune disorders involved in pathogenesis of psoriasis and PsA are those characterized by alterations of Th1-type cytokine profile (TNFα, IL-2, IFNγ, etc.). We have analyzed publications that reveal some features of PS and PsA immunopathogenesis associated with nature of the diseases. The review draws attention to relatively new and scarcely studied data concerning the role of cytokines produced by Th17- and Th22-cells (IL-17, IL-22, IL-23, IL-26), IL-19 subfamily (IL-19, IL-20, IL-24) in development of psoriasis and PsA. Search for the immunological markers predisposing for risk of psoriasis and PsA is an important step in personalized approach to their prediction and planning of preventive measures, in order to prevent progression of this pathology.